Nutrient additions to seagrass seed planting improve seedling emergence and growth - Unsworth, R.K.F.; Rees, S.C.; Bertelli, C.M.; Esteban, N.E.; Furness, E.J.; Walter, B. (Frontiers in Plant Science, 2022)
To maximise the opportunities of seagrass as a nature-based solution requires restoration to occur on a large scale. New methods and knowledge are required that can solve ecological bottlenecks, improving its reliability and effectiveness. Although there is increasing interest in the use of seeds for seagrass restoration there exists a limited understanding of how best to plant them with the most knowledge on germination and seedling emergence coming from laboratory studies. Here we present the results of a novel field study on the emergence success of seeds of the seagrass Zostera marina when subjected to varied planting treatments. Seeds were planted into hessian bags according to a factorial design of three treatments (sediment type, detritus addition, and nutrient addition) each replicated 12 times. By adding nutrients to natural sediment, the present study provides some evidence of seagrass shoot emergence and maximum shoot length doubling. The present study provides evidence that even in heavily nutrient-rich environments, seagrass sediments may require additional nutrients to improve seedling emergence and growth. It also highlights the highly variable nature of planting seagrass seeds in shallow coastal environments. Critically this study provides increasing levels of evidence that small subtleties in the method can have large consequences for seagrass restoration and that for restoration to scale to levels that are relevant for nature-based solutions there remain many unknowns that require consideration.